An interpersonal approach to classroom management strategies for improving student engagement - Davis, Heather A.; Summers, Jessica J.; Miller, Lauren M.; Sage eBooks (Thousand Oaks, Calif. : Corwin Press/A Joint Publication, 2012)
'An Interpersonal Approach to Classroom Management' contrasts how two teachers respond differently to common situations. The authors expertly bridge the gap between educational psychology and peer and student-teacher management from the perspectives of student engagement, classroom relationships, and teacher self regulation. Both current and prospective teachers will find helpful tools for exploring their beliefs, motivating students, and responding to conflict.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Classroom management; Teacher-student relationships; Educational psychology; Electronic books